Industrial development in the North – Sámi interests squeezed between globalization and tradition - Angell, Elisabeth; Nygaard, Vigdis; Selle, Per (Acta Borealia, 2020)
In this article, we analyse tensions in Sámi local communities meeting new industrial development. Indigenous communities experience outmigration and are in need of new business development and employment. Global extractive companies may offer new jobs, but the type and scale of these jobs put pressure on traditional indigenous livelihoods. The study underlines the importance of two core ideal type Sámi positions – traditionalist and modernist – on future industrial development in rural Sámi areas in Norway. These positions are playing themselves out in different ways by the most important Sámi institutions; The Sámi Parliament (Sámediggi), The Finnmark Estate (FeFo) and Sámi-populated municipalities. The result is a deep-going institutional conflict around industrial development, making it very difficult to find compromises. To shed light on these conflicts and their implications, we analyse how different positions are institutionally visible in the ongoing battle concerning the Nussir mining case in the Sámi municipality Kvalsund in Northern Norway. publishedVersion